Dinamika Jasa Pendidikan Dan Pentingnya Pemasaran Jasa Pada Pendidikan - Abdullah Muqopie; Najmi Muhajir, Nur Muhammad; Mu’in, Abdul (Universitas Islam Kiai Haji Achmad Siddiq Jember, 2023)
Marketing in the broadest sense is setting goals for accumulating profits to achieve the goals of an organization or institution, an understanding that is oriented towards accumulating profits, making the goal setting in question oriented towards market or customer needs whose ultimate goal is accumulating profits. Marketing education here is defined not as an organization or institution, but education is classified as a